The Effects of a Peer Mentoring Program on Academic Success Among First Year University Students - Rodger, Susan; Tremblay, Paul F. (Canadian Journal of Higher Education, 2003)
The present study examines the effect of participation of first-year university students in a full-year peer mentoring program as well as individual differences in motivation in relation to outcome measures of retention and achievement. A sample of 983 first year students completed the Academic Motivation Inventory (Tremblay, 1998) and agreed to provide final grades; 537 students were randomly assigned to participate in the program, while the remainder served as a control group. Mentored students who continued to participate mid-way through the second semester had significantly higher final grades than did students in the control group. There was no effect on retention from year one to year two, however data are being collected on retention and grades for all groups for the length of their undergraduate careers. Students high in anxiety in the mentored group showed achievement comparable to that of low anxiety program participants, whereas students in the control group with high anxiety scored significantly worse on achievement than did their low anxiety counterparts.